Differential modulation in metabolites revealed with the improvement in the shelf-life of alphonso fruits - Dar, M. Saleem; Dholakia, Bhushan B.; Shanmugam, Haripriya; Gupta, Vidya S.; Subramanian, K. S.; Subramanian, J.; Giri, Ashok P. (Molecular Biotechnology, 2020)
Globally farmers have difficulty in extending the shelf-life of the tropical fruits due to their perishable nature. The present study aimed to assess the effect of hexanal nano-formulation treatment (NFT) on the shelf-life of Alphonso mango. Further, volatilomics was performed to explore the molecular basis of such effect. Untreated and treated fruits were sampled starting from 5th to 21st day after NFT at an interval of 4 days. Moderate changes in visual and digital colour parameters were evident from the intact and dissected fruits of NFT set compared to untreated fruits. Biochemical assays affirmed the phenotypic differences with significant changes in the colour imparting compounds like carotenoids and anthocyanins among them. Further, gas chromatography-mass spectrometry analysis revealed significant qualitative and quantitative variations in the different classes of compounds like lactones, furanones, esters, aldehydes and alcohols. Some of the key metabolites showed differential modulations among the NFT and untreated fruit sets indicating their potential role in various processes, which ultimately might have resulted in delayed ripening of the mango. Overall, this study has demonstrated the beneficial effect of hexanal and identified important metabolites with the enhanced shelf-life in Alphonso that could be useful for farmers and mango-based food/flavour industries.
Keywords: Alphonso; GC-MS; Metabolites; Nano-biotechnology; Nano-formulation; Shelf-life; Volatilomics

Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste